PENGEMBANGAN DESAIN MEDIA PEMBELAJARAN BERBASIS KATALOG PENINGGALAN SEJARAH LOKAL UNTUK MENGUATKAN PEMAHAMAN SEJARAH LOKAL SISWA DI SMA NEGERI 3 MENGGALA TULANG BAWANG - Dika Agustina; Kian Amboro (Swarnadwipa, 2018)
The purpose of this research is to find the media of Learning Media catalog which can give information briefly, regularly and clearly about the material of history of war against colonialism, the time of arrival process and the power of VOC, and the impact of Dutch government in class XI, and in class X the impact in spreading Islam and also aims to strengthen the understanding of local history of the students. This type of research is a Level 1 development which is where in the preparation of this medium with the development method Sugiyono level 1 which where only test the feasibility of the product with internal validating stage by the team of experts not to the stage test try to students, with the preparation must also be adjusted with the analysis KI, KD and the subject matter, after the drafting process is completed then the next stage can be validated internally by a team of material and media experts.Based on the results of research, has been obtained instructional media based local historical heritage in Menggala Tulang Bawang which has been through the validation stage, validation is a media feasibility test developed, validation is through two stages of stage 1 and 2, which of course there are suggestions and comments in order to revise the product back up to the criteria worth at least score 81 and from the data obtained on the validation of material and media experts there is an increase in scores at stages 1 and 2, in stage 1 the material got a percentage of 78% and in stage 2 with the value 88% percentage. While the validation of media experts in stage 1 got the percentage of 80% and in stage 2 got a percentage of 94%. From these data can already be declared feasible tested